Cobertura e depósito de calda fitossanitária em plantas de café pulverizadas com equipamento original e adaptado para plantas altas - Ferreira, Marcelo da Costa [UNESP]; Leite, Gilson Jose [UNESP]; Lasmar, Olinto [UNESP] (Univ Federal Uberlandia, 2013)
The objective of this study was to evaluate the coverage of spray droplets on coffee plants as well as their deposition using a sprayer with and without adaptation of an auxiliary branch for tall plants. The experiment was conducted following a randomized block design with six treatments and four replications to evaluate the percentage of coverage for the spraying liquids in water sensitive paper fixed at four quadrants and two heights (lower and upper) of the plants, and the spray deposit with metallic marker (MnSO4) on sheets in the same positions of the water sensitive paper in two spray volumes (450 and 750 L h(-1)). The experiment was conducted in October 2011 in the town of Patroc nio-MG, and the experimental plots consisted of 30 plants of Catua IAC-99, with approximately 12 years of age and average height of 3.50 meters. The experiments were conducted following a randomized block design with six treatments and four replications to evaluate the coverage and deposition, in two spray volumes (450 and 750 L ha(-1)). Leaves were collected in four positions and also at the top four in the lower canopy. The results of the evaluations were analysed statistically by F test and for comparison of means by Tukey test at 5% probability. The auxiliary branch installed at the rear of the equipment is the most suitable when compared to use of equipment without this feature or installed in the front of the equipment. Furthermore, the application volume of 450 L ha(-1) results in coverages and deposits of spraying liquids equivalents to volume of 750 L ha(-1), considered sufficient according to the parameters evaluated.

O objetivo deste trabalho foi avaliar a cobertura de gotas de pulverização sobre plantas de café bem como o seu depósito utilizando um pulverizador com e sem adaptação de um ramal auxiliar para plantas altas. O experimento foi realizado em outubro de 2011, no município de Patrocínio-MG, sendo as parcelas experimentais constituídas de 30 plantas da variedade Catuaí IAC-99, com aproximadamente 12 anos de idade e altura média de 3,50 metros. O experimento foi instalado seguindo um delineamento de blocos ao acaso com seis tratamentos e quatro repetições para avaliar o percentual de cobertura pela calda em papel hidrossensível fixado em quatro quadrantes e duas alturas (inferior e superior) das plantas e o depósito de calda com marcador metálico (MnSO4) sobre folhas, nas mesmas posições do papel hidrossensível, em dois volumes de aplicação (450 e 750 L ha-1). Foram realizadas coletas de folhas em quatro posições no alto e também quatro na parte baixa da copa. Os resultados das avaliações realizadas foram analisados estatisticamente pelo Teste F e, para comparação das médias, pelo teste de Tukey a 5% de probabilidade. O ramal auxiliar instalado na parte de trás do equipamento é a forma de utilização mais indicada, em ralação à instalação na posição dianteira ou ao não uso deste recurso, bem como o volume de aplicação de 450 L ha-1 resulta em coberturas e depósitos de calda equivalentes ao volume de 750 L ha-1, considerado suficiente segundo os parâmetros avaliados.
Coverage and deposition of spraying liquids in coffee plants sprayed with original equipment and adapted to tall plants
Keywords: Application technology; Coffea arabica; Development; Spray